Prof. V. C. Kulandai Swamy-An Educationlist - Kulandai Swam, V. C. (Journal of Engineering Education Transformations, 1995)
Prof. V. C. KuJandai Swamy obtained M.Tech. from I.I.T., Kharagpur and Ph.D. in Hydrology and Water Resources, from the University of Illinois, U.s.A. Starting his career as a teacher and researcher, he was Lecturer, Asst. Professor, Professor and Dean of Post Graduate Studies in the College of Engineering (now Anna University), Madras. He has made outstanding contributions in Hydrology.